Comparison of Team Sports and Individual Sports on Health Status and Emotional Intelligence of Children Aged 13-16 Years - Gandang Eka Prayoga; Anung Priambodo; Noortje Anita Kumaat (BIRCU, 2022)
This study aims to determine the comparison of team sports and individual sports on the health status and emotional intelligence of children aged 13-16 years. In this study, the research method used is a quantitative approach with experimental research methods. The data analysis technique used MANOVA. The data collection process was carried out using a questionnaire instrument, namely the KIDSCREEN-27 questionnaire to measure health status and the Trait Emotional Intelligence Questionnaire-Adolescent Short Form was used to measure emotional intelligence. Then the data is processed using the SPSS version 22.0 application. The results showed: (1) There was a significant difference between team sports and individual sports on the health status of children aged 13-16 years with a significant value of 0.007 < 0.05; (2) There is no difference in the effect of team sports and individual sports on the emotional intelligence of children aged 13-16 years with a significant value of 0.918 > 0.05.